Inclusive Development in Indonesia: Integration of Islamic Business Management and Islamic Social Finance Based on Pancasila Values - Haryati, Haryati; Mughits, Abdul (Relevance: Journal of Management and Business, 2025)
This research aims to examine the integration between Islamic business management and Islamic social finance within the framework of Pancasila values as a strategy to build an inclusive development paradigm in Indonesia. Inclusive development is an important approach in dealing with socio-economic inequality, structural poverty and financial exclusion. This research applies a literature study method with a qualitative normative approach to analyze the basic principles underlying the policy and provide applicable recommendations in the context of an equitable and sustainable Islamic economy. Data was collected through a secondary literature review from reliable sources, including scientific journals, books, and official documents published between 2020-2025. The analysis process was carried out through three stages: data reduction, presentation of findings in the form of narratives and visualizations, and verification and conclusion drawing in a qualitative descriptive manner. The results show that the integration of these values forms an ethical and normative basis for equitable and sustainable economic governance. The Islamic business management model that integrates Islamic work ethics and maqashid al-syari'ah principles has a strong meeting point with the values of Pancasila in building a participatory economic system. Islamic social finance instruments such as zakat, waqf, and BMT have proven effective in expanding financial inclusion and empowering marginalized groups. This study recommends strengthening value-based policies, civil society participation, and economic and spiritual literacy as strategic steps in building an economic ecosystem oriented towards collective welfare and sustainability.